Two to Tango: Kidney-Lung Interaction in Acute Kidney Injury and Acute Respiratory Distress Syndrome - Alge, Joseph; Dolan, Kristin; Angelo, Joseph; Thadani, Sameer; Virk, Manpreet; Akcan Arikan, Ayse (Frontiers in Pediatrics, 2021)
Acute Kidney Injury (AKI) is an independent risk factor for mortality in hospitalized patients. AKI syndrome leads to fluid overload, electrolyte and acid-base disturbances, immunoparalysis, and propagates multiple organ dysfunction through organ “crosstalk”. Preclinical models suggest AKI causes acute lung injury (ALI), and conversely, mechanical ventilation and ALI cause AKI. In the clinical setting, respiratory complications are a key driver of increased mortality in patients with AKI, highlighting the bidirectional relationship. This article highlights the challenging and complex interactions between the lung and kidney in critically ill patients with AKI and acute respiratory distress syndrome (ARDS) and global implications of AKI. We discuss disease-specific molecular mediators and inflammatory pathways involved in organ crosstalk in the AKI-ARDS construct, and highlight the reciprocal hemodynamic effects of elevated pulmonary vascular resistance and central venous pressure (CVP) leading to renal hypoperfusion and pulmonary edema associated with fluid overload and increased right ventricular afterload. Finally, we discuss the notion of different ARDS “phenotypes” and the response to fluid overload, suggesting differential organ crosstalk in specific pathological states. While the directionality of effect remains challenging to distinguish at the bedside due to lag in diagnosis with conventional renal function markers and lack of tangible damage markers, this review provides a paradigm for understanding kidney-lung interactions in the critically ill patient.